Preparation, Photocatalytic Activity, and Recovery of Magnetic Photocatalyst for Decomposition of Benzoic Acid. (18th December 2011) - Su, Te-Li; Chiou, Chyow-San; Chen, Hua-Wei
Abstract : The purpose of this paper is to determine the experimental parameters of TiO2 preparation for optimizing the removal rate of benzoic acid by magnetic photocatalytic oxidation process. Therefore, this paper intended to prepare a magnetic photocatalyst (TiO2 /SiO2 /Fe3 O4 ) that can be recycled using an external magnetic field. Magnetic photocatalysts are characterized by X-ray diffraction (XRD), vibrating sample magnetometry (VSM), and Fourier transform infrared (FTIR) spectroscopy. The optimal the experimental parameters of TiO2 preparation for the removal rate of photocatalysts were concluded as pH is 3, weight ratio of TiO2 /SiO2 (Fe3 O4 ) is 1, and calcined temperature of TiO2 /SiO2 /Fe3 O4 is 350 ∘ C. Furthermore, the paramagnetic behaviors of the prepared TiO2 /SiO2 /Fe3 O4 gave rise to the magnetic photocatalyst, which could be separated more easily through the application of a magnetic field for reuse.